Development of Interactive Powerpoint-Based IPAS Learning Media on the Material of Plant Sources of Life on Earth for Class IV SD Negeri Tugurejo 02 Semarang City - Marsya Fatkhia Nurani; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2024)
This study was conducted to develop, test the feasibility and effectiveness of interactive powerpoint-based IPAS learning media on the material of Plant Sources of Life on Earth to improve student learning outcomes. This research uses the ADDIE model. The sampling technique used nonprobability sampling technique, namely purposive sampling. Data collection techniques through tests and non-tests. The results of the product validation test by media expert validators obtained a percentage of 93.3% in the